2021
DOI: 10.1128/aem.02719-20
|View full text |Cite
|
Sign up to set email alerts
|

Mannose- and Mannobiose-Specific Responses of the Insect-Associated Cellulolytic Bacterium Streptomyces sp. Strain SirexAA-E

Abstract: The cellulolytic insect symbiont bacterium, Streptomyces sp. SirexAA-E (SirexAA-E) secretes a suite of Carbohydrate Active enZymes (CAZymes), which are involved in the degradation of various polysaccharides in the plant cell wall, in response to the available carbon sources. Here, we examined a poorly understood response of this bacterium to mannan, one of the major plant cell wall components. SirexAA-E grew well on mannose, carboxymethyl cellulose (CMC), and locust bean gum (LBG) as sole carbon sources in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…In particular, the abundance of Streptomyces was higher in the DPBOS than PEBOS treatment in non-rhizosphere soil. Streptomyces is able to degrade cellulose, pesticides, and petroleum compounds (Chen et al 2020 ; Ohashi et al 2021 ; Santillan et al 2020 ). Further, Streptomyces may be critically involved in plastics’ degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the abundance of Streptomyces was higher in the DPBOS than PEBOS treatment in non-rhizosphere soil. Streptomyces is able to degrade cellulose, pesticides, and petroleum compounds (Chen et al 2020 ; Ohashi et al 2021 ; Santillan et al 2020 ). Further, Streptomyces may be critically involved in plastics’ degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting Streptomyces as a sharing species our analysis identified mannobiose as a metabolite that was much more abundant when Streptomyces was present vs. in a community lacking Streptomyces . This C source has been shown to be produced by Streptomyces and consumed by Rhodococcus ( Ohashi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In total, in 182 Streptomyces strains, 4403 LacI TFs were identified, grouped into 167 COGs. Among these, only 5 (~3% of all LacI TFs) have been subject to studies in Streptomyces species, i.e., i) the galactomannan/mannobiose/mannose utilization repressor ManR (LacI003 in Table 1, conserved in 177/182 species) (Ohashi et al, 2021), (ii) the maltose/maltodextrin catabolism pathway regulator MalR (LacI005 in Table 1, conserved in 176/182 species) (Nguyen, 1999;Nguyen et al, 1997;Schlösser et al, 2001;van Wezel, White, Bibb, et al, 1997;van Wezel, White, Young, et al, 1997), iii) the cellulose/cello-oligosaccharide utilisation regulator CebR (LacI006 in Table 1, conserved in 153/182 species) (Book et al, 2016;Francis et al, 2015;Jourdan et al, 2016;Marushima et al, 2009;Schlösser et al, 2000), iv) the xylan/xylo-oligosaccharide utilization repressor BxlR (LacI015 in Table 1, conserved in 88/182 species) (Giannotta et al, 1996(Giannotta et al, , 2003Tsujibo et al, 2004), and v) the agar-utilisation regulator DagR (LacI139 in Table 1) (Tsevelkhoroloo et al, 2021), the latter being one of the rarest LacI TF, only conserved in two Streptomyces species. Strikingly, the function of the two most conserved LacI TFs (LacI001 and LacI002 in Table 1) is unknown, further illustrating the lack of knowledge about transcriptional regulation in this well-studied bacterial genus.…”
Section: Laci-family Transcription Factor Identificationmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 10, 2022. ; https://doi.org/10.1101/2022.04.06.487287 doi: bioRxiv preprint to their experimentally identified consensus sequences, i.e., GACAACGTTGTC (Ohashi et al, 2021), TGGGAGCGCTCCCA (Schlösser et al, 2000), and CGAA-Nx-TTCG (Giannotta et al, 1996(Giannotta et al, , 2003Tsujibo et al, 2004), respectively. For MalR (LacI005), the two binding sites deduced by DNase footprinting assays (Schlösser et al, 2001) were also found (see Table 1), further confirming that our approach is appropriate for deducing over-represented motifs that closely relate to the ones that were experimentally identified.…”
Section: Identification Of Tf Binding Sitesmentioning
confidence: 99%
See 1 more Smart Citation